2019
DOI: 10.1007/s40430-019-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation and self-diffusion research about dry granular materials under shearing

Abstract: Flow and self-diffusion behaviors of granules in sheared granular systems are a typical study field but still not yet fully grasped because of the complexities and discreteness of granular matter systems. This paper presents a discrete element method-based simulation research of the fluctuation and self-diffusion characteristics of granules in a dense sheared granular system. Simulation results show that the average velocity of granules decreases with the altitude location, which is reverse to the variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…They concluded that the fluctuation of a single particle is strongly connected to the system's overall velocity. Similar investigations have been conducted by Meng et al [22], who established that the boundary effect influences the fluctuation of local particles. Lu et al [23] conducted a discrete element simulation of overland flow and demonstrated that there exists a considerable correlation between the dynamic characteristic fluctuation of the particle flow system and the system particle size.…”
Section: Introductionsupporting
confidence: 75%
“…They concluded that the fluctuation of a single particle is strongly connected to the system's overall velocity. Similar investigations have been conducted by Meng et al [22], who established that the boundary effect influences the fluctuation of local particles. Lu et al [23] conducted a discrete element simulation of overland flow and demonstrated that there exists a considerable correlation between the dynamic characteristic fluctuation of the particle flow system and the system particle size.…”
Section: Introductionsupporting
confidence: 75%
“…Methods that can be used to display force chains include the pressure sensor detection method [10], the color-sensitive carbon paper indentation method [11], the photoelastic method [6], and the DEM [12]. The DEM is one of the easier methods to realize the distribution of force chains and can obtain content that cannot be obtained through theoretical methods and conventional experiments [13][14][15][16]. Xu et al [17] used the DEM to complete the unloading process of nonsticky soft and sticky hard particles in the moving bed of a simulated flat-bottomed bin.…”
Section: Introductionmentioning
confidence: 99%
“…Granules have the characteristics of strong dissipation and insensitivity to high temperature, so that the granular flow lubrication is a perfect fit for these circumstances (Wang et al, 2014a(Wang et al, , 2014bPodgornik et al, 2015). Further studies have shown that hard, dry and cohesionless granules can be used as lubricants to reduce the friction and wear of the friction pairs (Timm et al, 2011;Meng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations via the discrete element method have advantages of simpler programming language, faster computing speed, having not convergence problem as well as having parallel computing function. Meanwhile, Simulations via the discrete element method can provide a lot of information both at the macroscopic and microscopic levels at any time during simulations, so this enables us to fully evaluate the response results (Meng et al, 2019, Khalilitehrani et al, 2017.…”
Section: Introductionmentioning
confidence: 99%